1991
DOI: 10.1073/pnas.88.23.10624
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and severity of cyclic flow alternations and platelet aggregation predict the severity of neointimal proliferation following experimental coronary stenosis and endothelial injury.

Abstract: Frequency and severity of cyclic flow alternations and platelet aggregation predict the severity of neointimal proliferation following experimental coronary stenosis and endothelial injury ( ABSTRACTThe role of recurrent platelet aggregation in the development of neointimal proliferation of coronary arteries was explored in this study, and the hypothesis was evaluated that recurrent platelet aggregation and the consequent frequency and severity of cyclic coronary blood flow variations are important pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(40 citation statements)
references
References 32 publications
1
35
0
4
Order By: Relevance
“…However, previous studies (25,27) have shown that adenoviral gene transfer of TFPI exerts significant protection against the development of cyclic flow reductions, in accordance with reports that administration of recombinant TFPI markedly reduced the procoagulant properties of balloon-injured rabbit arteries (32,33). We therefore speculate that local gene transfer of TFPI may prevent intimal hyperplasia, at least in part, by decreasing the local burden of thrombusdependent growth factors (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies (25,27) have shown that adenoviral gene transfer of TFPI exerts significant protection against the development of cyclic flow reductions, in accordance with reports that administration of recombinant TFPI markedly reduced the procoagulant properties of balloon-injured rabbit arteries (32,33). We therefore speculate that local gene transfer of TFPI may prevent intimal hyperplasia, at least in part, by decreasing the local burden of thrombusdependent growth factors (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of intimal hyperplasia after vascular injury is believed to involve diverse signaling cascades that ultimately converge on vascular smooth muscle cells (VSMC), stimulating their proliferation and migration and their prolonged secretion of extracellular matrix (1,2). Thrombus formation at the site of injury contributes to reobstruction of the vessel through its bulk and through the release of growth and chemotactic factors that further promote accumulation of intimal VSMC (1)(2)(3). Proteins involved in blood clotting, including the tissue factor (TF)͞fac-tor VIIa complex, factor Xa, and thrombin (4-6), exert chemotactic and mitogenic activity on VSMC and other cells.…”
mentioning
confidence: 99%
“…Plaque passivation could be explained by better dissolution of the thrombus, which is by itself a powerful thrombogenic stimulus. 13 Additional mechanisms could be prevention of the release of platelet-active products associated with cell proliferation 27 and prevention of platelet-leukocyte interaction. 28 The impaired outcome associated with persistence of thrombus has important implications for patient management.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin -Clinical studies [28][29][30] artery stenosis and endothelial injury. Activated platelets release serotonin in substantial quantities causing vasoconstriction and recurrent aggregation of platelets with cyclic flow reductions.…”
Section: Discussionmentioning
confidence: 99%